Implementing Inquiry Learning Model to Improve Primary Studentsâ Critical Thinking Skills in Science Learning - Kinanti, Dyah Ayu; Eriyanti, Eriyanti; Haerani, Haerani; Alpusari, Mahmud; Hermita, Neni (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research aims to improveprimary studentsâ critical thinking skill through inquiry learning model in science learning. This research was classroom action research in two cycles with consist of planning, action, observation, and reflection. Each cycle consisted of two sessions. Data collection techniques were non-test and test. Data were analyzed using quantitative and qualitative analysis. The results of the research show the percentage of the critical thinking skill outcomes in first cycle is 66.67 % and second cycle is 80.55 %. The average teacherâs skill in first cycle scored 26 (good category) and second cycle scored 33 (excellent category). The average in studentâs activity first cycle scored 69 (good category) and second cycle scored 91 (excellent category). In conclusion, implementing inquiry learning model can improve critical thinking skill primary studentsâ critical thinking skill.